Biological monitoring of occupational exposure to toluene diisocyanate: measurement of toluenediamine in hydrolysed urine and plasma by gas chromatography-mass spectrometry. Issue 12 (December 1993) - Persson, P; Dalene, M; Skarping, G; Adamsson, M; Hagmar, L
Abstract : Exposure to toluene diisocyanate (TDI) was studied during 48 hours and biological samples from nine subjects were taken in a factory producing flexible polyurethane (PUR) foam. Five PUR workers, two white collar workers, and two volunteers were studied. The concentrations of TDI in air were determined by high performance liquid chromatography with the 9-(N-methylaminomethyl)-anthracene reagent. Urine and plasma samples were collected and the TDI related amines, 2, 4-toluenediamine (2, 4-TDA) and 2, 6-toluenediamine (2, 6-TDA), were determined (after hydrolysis) as pentafluoropropionic anhydride (PFPA) derivatives by capillary gas chromatography-mass spectrometry (GC-MS) with selected ion monitoring (SIM) in the negative chemical ionisation mode. The concentration of TDI in air was 1%-10% of the Swedish threshold limit value (TLV) of 40 micrograms/m3. The ratio between 2, 4-TDI and 2, 6-TDI varied in the air samples in the range of 60%:40%-5%:95%. Calibration plots for human urine spiked with 2, 6-TDA and 2, 4-TDA in the range of 0.2-12 micrograms/l were produced on eight different occasions during five weeks. The SDS of the calibration plot slopes (n = 8) were less than 4%. Urine and blood samples were taken on six occasions for eight of the studied subjects and on four occasions for one subject during a two day period. The five male PUR workers showed the highest average urinary elimination rate of TDA. Two PUR workers and the two white collar workers had an elimination rate of 20-70 ng on average for the sum of 2, 6-TDA and 2, 4-TDA per hour and three PUR workers had an average of 100-300 ng TDA per hour. The elimination rate curves for all the studied subjects had a linear relation with exposure to TDI. The concentrations of 2, 4-TDA and 2, 6-TDA in plasma for the PUR factory employees were virtually stable. No relation between the elimination rates of TDA in urine and plasma concentrations of TDA was found. The five PUR workers showed plasma concentrations of the sum of 2, 4-TDA and 2, 6-TDA in the range 1-8 ng per ml. The two white collar workers, present only on occasions in the factory, had 0.2- ng TDA per ml plasma. The two volunteers showed an increasing concentration of TDA in plasma with time. At the end of the study their plasma concentrations were 0.6 ng/ml and 0.2 ng/ml plasma. Three subjects had the same concentration of the two TDA isomers in plasma, two subjects had about double, and two subjects had 12 times higher concentrations of 2, 6-TDA than 2, 4-TDA. The presented study indicates that it is possible to monitor exposure to TDI by monitoring plasma concentrations of TDA.